Potential Application of Electrical Stimulation in Stem Cell-Based Treatment against Hearing Loss. (8th May 2018) - Tang, Mingliang; Yan, Xiaoqian; Tang, Qilin; Guo, Rongrong; Da, Peng; Li, Dan
Abstract : Deafness is a common human disease, which is mainly caused by irreversible damage to hair cells and spiral ganglion neurons (SGNs) in the mammalian cochlea. At present, replacement of damaged or missing hair cells and SGNs by stem cell transplantation therapy is an effective treatment. However, the survival rate of stem cell transplantation is low, with uncontrollable differentiation hindering its application. Most researchers have focused on biochemical factors to regulate the growth and differentiation of stem cells, whereas little study has been performed using physical factors. This review intends to illustrate the current problems in stem cell-based treatment against deafness and to introduce electric field stimulation as a physical factor to regulate stem cell behavior and facilitate stem cell therapy to treat hearing loss in the future.